Bencana Likuifaksi Dalam Perspektif Al-Qur’an Dan Sains (Analisis Kesesuaian Tafsir Ilmi dan Sains Modern) - Yuspitasari, Selvy (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
Through descriptive qualitative methods and types of library research, found a match between the scientific theories and opinions of commentators about the verses of the Qur'an which explain changes in soil structure that cause submersion earth, it is explained that the statement or interpretation that is most approaching the theory of science, contained in the book Tahrir wa tanwir namely al-Khasfu which means the upside of the earth's surface, which is above and below and the bottom of the earth is above it this is because shaking or earthquake.